The stab-in-the-back myth and the fall of the Weimar Republic : a history in documents and visual sources - Vascik, George S. 1988- Herausgeber; Sadler, Mark R. 2009- Herausgeber (Bloomsbury Academic, 2016)
"A broad range of primary documents and visual sources exploring the Stab-in-the-Back myth, its role in the end of the Weimar Republic and its impact on the Nazi regime that followed"--